HSP27 Protein Dampens Encephalomyocarditis Virus Replication by Stabilizing Melanoma Differentiation-Associated Gene 5 - Li, Xiangrong; Ma, Ruixian; Wu, Bei; Niu, Yuhui; Li, Hongshan; Li, Dianyu; Xie, Jingying; Idris, Adi; Feng, Ruofei (Frontiers in Microbiology, 2021)
Heat shock proteins (HSPs) are a protein family that responds to physiological stress, such as heat, starvation, and infection. As cellular protein chaperones, they play an important role in protein folding, assembly, and degradation. Though it is well known that HSP27 is involved in a range of viral infections, its role during an encephalomyocarditis virus (EMCV) infection is not known. Here, we report that EMCV degrades HSP27 and that EMCV proteins 2Cpro and 3Apro are primarily responsible for its degradation. Consequently, loss of cellular HSP27 augmented EMCV proliferation, an effect that could be reversed upon HSP27 overexpression. Importantly, we found that HSP27 positively regulated EMCV-triggered type Ⅰ interferon (IFN) production. Moreover, overexpression of 2Cpro and 3Apro significantly blocked type Ⅰ IFN production. We also found for the first time that HSP27, as a molecular chaperone, can specifically interact with MDA and stabilize the expression of MDA. Collectively, this study shows that HSP27 dampens EMCV infectivity by positively regulating EMCV-triggered RLR/MDA5 signal pathway, while EMCV proteins 2Cpro and 3Apro interact with HSP27 and degrade HSP27 protein expression to allow EMCV proliferation. Our findings provide further mechanistic evidence for EMCV partaking in immune escape mechanisms, and that 2Cpro and 3Apro could serve as potential antiviral targets.